DETERMINAN SOSIAL KESEHATAN DENGAN PERILAKU PHYSICAL DISTANCING PADA MAHASISWA - Widya Hary Cahyati; Daryati Daryati (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
COVID-19 cases in Indonesia on 22 November 2020 were 493,308 cases. Social determinants of health and behavior influence mortality and morbidity in a community. Physical-distancing is an effort to maintain a distance between one person and another to avoid transmission of the COVID-19 disease. The purpose of this study was to research about social health determinants with physical-distancing behavior during the Covid-19 Pandemic for Students. This research applied analytic observasional method with design of crosssectional, case study on students of Universitas Negeri Semarang. The sampling technique was used a probability sampling technique with a cluster sampling type with a total sample size of 235. The instrument used was a questionnaire. The results showed that gender (P=0.044, PR=1.155), knowledge level of Covid-19 (P=0.000, PR=2.508), family support (P=0.003, PR=1.710), support from community leaders (P=0.013, PR=1.311), government support (P=0.002, PR=1.854), and respondents' perceptions (P=0.000, PR=4.465) are related to physical distancing behavior. The social determinant most related to physical distancing behavior is the level of knowledge (P=0.000). The conclusion of this study is the level of knowledge is the most influential factor in physical distancing behavior in College Students of Universitas Negeri Semarang.